Activity and circadian rhythm influence synaptic Shank3 protein levels in mice. Issue 6 (15th July 2016) - Sarowar, Tasnuva; Chhabra, Resham; Vilella, Antonietta; Boeckers, Tobias M.; Zoli, Michele; Grabrucker, Andreas M.
Abstract: Various recent studies revealed that the proteins of the Shank family act as major scaffold organizing elements in the post‐synaptic density of excitatory synapses and that their expression level is able to influence synapse formation, maturation and ultimately brain plasticity. An imbalance in Shank3 protein levels has been associated with a variety of neuropsychological and neurodegenerative disorders including autism spectrum disorders and Phelan–McDermid syndrome. Given that sleep disorders and low melatonin levels are frequently observed in autism spectrum disorders, and that circadian rhythms may be able to modulate Shank3 signaling and thereby synaptic function, here, we performed in vivo studies on CBA mice using protein biochemistry to investigate the synaptic expression levels of Shank3α during the day in different brain regions. Our results show that synaptic Shank3 protein concentrations exhibit minor oscillations during the day in hippocampal and striatal brain regions that correlate with changes in serum melatonin levels. Furthermore, as circadian rhythms are tightly connected to activity levels in mice, we increased physical activity using running wheels. The expression of Shank3α increases rapidly by induced activity in thalamus and cortex, but decreases in striatum, superimposing the circadian rhythms of different brain regions. We conclude that synaptic Shank3 proteins build highly dynamic platforms that are modulated by the light:dark cycles but even more so driven by activity. Using wild‐type CBA mice, we show that Shank3 is a highly dynamic and activity‐regulated protein at synapses. In the hippocampus, changes in synaptic Shank3 levels are influenced by circadian rhythm/melatonin concentration, while running activity increases and decreases levels of Shank3 in the cortex and striatum respectively. Abstract : Using wild‐type CBA mice, we show that Shank3 is a highly dynamic and activity‐regulated protein at synapses. In the hippocampus, changes in synaptic Shank3 levels are influenced by circadian rhythm/melatonin concentration, while running activity increases and decreases levels of Shank3 in the cortex and striatum respectively.